Experimental Investigation on the Ecofriendly External Wrapping of Glass Fiber Reinforced Polymer in Concrete Columns. (29th August 2021) - Vijayan, D. S.; Mohan, A.; Jebasingh Daniel, J.; Gokulnath, V.; Saravanan, B.; Kumar, P. Dinesh
Abstract : An ecofriendly fiber reinforced polymer (FRP) had been used in the last decade to enhance the short concrete column's strength and deformation capacity. This study involves the wrapping of FRP sheets with a thickness of 3 mm and 5 mm on a short column, and then the compressive strength is determined. The rectangular columns of size 150 mm × 300 mm are used for this study, and cast under the grades of M20 and M40 are wrapped with GFRP sheets at the thickness of 3 mm and 5 mm. These results are clarified at a specific thickness of the FRP-wrapped columns. It provides a maximum axial compressive strength, and Young's modulus gets enhanced rigorously when it is to be compared to the normal concrete. This thesis deals with experimental studies of different parameters associated with wrapped glass fiber reinforced polymer (GFRP). In M20 grade, when the 3 mm wrapped specimen and the 5 mm wrapped specimen are compared, the specimen wrapped with 5 mm increases 5.182% more than the specimen wrapped with 3 mm. In M40 grade, when the 0 mm, 3 mm, and 5 mm wrapped specimens are compared, the specimen wrapped with 5 mm increases 2.47% more than the specimen wrapped with 0 mm. The 5 mm wrapping attains the maximum strength.